Redefining Primum Non Nocere to Include Reproductive Autonomy: A New Paradigm in Subspecialty Medicine - Mehret Birru Talabi; Lisa S. Callegari; Lisa S. Callegari; Sonya Borrero (Mary Ann Liebert, 2021)
People with chronic medical illnesses are at particularly high risk for adverse pregnancy outcomes, yet current clinical approaches largely fail to identify and support their individualized reproductive and pregnancy goals. Instead, the predominant approach to pregnancy in subspecialty medicine is disease centered rather than patient centered. To better meet the individual needs and preferences of people with childbearing potential who have chronic medical conditions, we advocate in this article for a paradigm shift in subspecialty care that honors individuals' reproductive autonomy and human right of reproduction.